Semiconductor lasers and diode-based light sources for biophotonics - Andersen, Peter E. 1967-; Petersen, Paul Michael (IET healthcare technologies series, 2018)
The book has 13 chapters. The book chapters are introduction to semiconductor light sources and their biomedical applications; fundamentals on modeling of edge-emitting semiconductor lasers and superluminescent light-emitting diodes; Q-switched and mode-locked lasers for biophotonic applications; light-emitting diode technologies; GaN-based blue vertical-cavity surface-emitting lasers; quantum cascade lasers; diode laser systems based on nonlinear frequency conversion; semiconductor disk lasers; potential biomedical use of diode-laser-induced luminescence from upconverting nanoparticles; near-infrared spectroscopy systems for biomedical applications; semiconductor lasers for bio-medical Raman spectroscopy; nonlinear imaging applications of high-power lasers - figures of merit; and optical coherence tomography.